Do Specialized Cells Play a Major Role in Organic Xenobiotic Detoxification in Higher Plants? - Cavé-Radet, Armand; Rabhi, Mokded; Gouttefangeas, Francis; El Amrani, Abdelhak (Frontiers in Plant Science, 2020)
In the present work, we used a double cell screening approach based on phenanthrene (phe) epifluorescence histochemical localization and oxygen radical detection to generate new data about how some specialized cells are involved in tolerance to organic xenobiotics. Thereby, we bring new insights about phe [a common Polycyclic Aromatic Hydrocarbon (PAH)] cell specific detoxification, in two contrasting plant lineages thriving in different ecosystems. Our data suggest that in higher plants, detoxification may occur in specialized cells such as trichomes and pavement cells in Arabidopsis, and in the basal cells of salt glands in Spartina species. Such features were supported by a survey from the literature, and complementary data correlating the size of basal salt gland cells and tolerance abilities to PAHs previously reported between Spartina species. Furthermore, we conducted functional validation in two independent Arabidopsis trichomeless glabrous T-DNA mutant lines (GLABRA1 mutants). These mutants showed a sensitive phenotype under phe-induced stress in comparison with their background ecotypes without the mutation, indicating that trichomes are key structures involved in the detoxification of organic xenobiotics. Interestingly, trichomes and pavement cells are known to endoreduplicate, and we discussed the putative advantages given by endopolyploidy in xenobiotic detoxification abilities. The same feature concerning basal salt gland cells in Spartina has been raised. This similarity with detoxification in the endopolyploid liver cells of the animal system is included.